2019
DOI: 10.1002/mgg3.536
|View full text |Cite
|
Sign up to set email alerts
|

Molecular diagnosis of somatic overgrowth conditions: A single‐center experience

Abstract: Background Somatic overgrowth conditions, including Proteus syndrome, Sturge–Weber syndrome, and PIK3CA ‐related overgrowth spectrum, are caused by post‐zygotic pathogenic variants, result in segmental mosaicism, and give rise to neural, cutaneous and/or lipomatous overgrowth. These variants occur in growth‐promoting pathways leading to cellular proliferation and expansion of tissues that arise from the affected cellular lineage. Methods We re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 18 publications
3
23
0
Order By: Relevance
“…In contrast to peripheral blood, buccal swabs (comprised primarily of epithelial cells and leukocytes 41 ) are often perceived as an unaffected tissue type, with studies indicating that P/LP variants are rarely detected from buccal swabs and that the VAFs of the detected variants tend to be low. 34 In our experience, however, the rate of findings was similar to more invasive specimen types in case subjects with disease findings involving the head, even in those without obvious macrocephaly and brain malformations (e.g., macroglossia, hemihypertrophy of the face [MIM: 133900], nevi on the head, etc.). , white dots represent case subjects from which the P/LP variant was found only in the affected sample (confirmed somatic), and gray dots represent case subjects for which no peripheral blood was submitted.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…In contrast to peripheral blood, buccal swabs (comprised primarily of epithelial cells and leukocytes 41 ) are often perceived as an unaffected tissue type, with studies indicating that P/LP variants are rarely detected from buccal swabs and that the VAFs of the detected variants tend to be low. 34 In our experience, however, the rate of findings was similar to more invasive specimen types in case subjects with disease findings involving the head, even in those without obvious macrocephaly and brain malformations (e.g., macroglossia, hemihypertrophy of the face [MIM: 133900], nevi on the head, etc.). , white dots represent case subjects from which the P/LP variant was found only in the affected sample (confirmed somatic), and gray dots represent case subjects for which no peripheral blood was submitted.…”
Section: Discussionsupporting
confidence: 69%
“…Previous studies have stressed the importance of testing disease-affected tissues. 9,25,34 Upon review of test requisitions and other medical records, 301 of the 358 submitted specimens were deemed to be representative of disease-affected tissues. We identified P/LP variants in 65% of these affected specimens compared to just 4 of 57 unaffected tissue specimens.…”
Section: Impact Of Specimen Selectionmentioning
confidence: 99%
“…Then, mosaicisms were recognized as other causative mechanisms of overgrowth syndromes, and several of the genes involved, including AKT1, PTEN, and PIK3CA, have been identified [21][22][23]. Some reports found that the rate of detection of somatic mosaicism in overgrowth syndromes improved using high-sensitivity sequencing with specimens of the affected tissues rather than peripheral blood [23][24][25][26]. Here, we selected a group of patients who met strict phenotypic diagnostic criteria of MCAP and conducted high-depth target gene sequencing, mostly with affected tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Testing consisted of methylation‐sensitive, quantitative, real‐time polymerase chain reaction (PCR) of bisulfite‐treated DNA to evaluate methylation levels at IC1 and IC2 22 and a comparative genomic hybridization and single‐nucleotide polymorphism array (SNP) to identify copy number changes and uniparental disomy at 11p15.5, with reflex to Sanger sequencing of the CDKN1C gene if methylation and copy number and/or SNP analysis were normal 23,24 . Briefly, 2 independent DNA isolates were collected from each submitted sample for testing and DNA was isolated as previously described 25 . Evaluation of polymorphic short tandem repeats to verify that both independent DNA isolates were collected from the same individual was performed for quality control as described 26 .…”
Section: Methodsmentioning
confidence: 99%